Respuestas
Respuesta dada por:
1
1) 90 = (X + 1)(90 - X/X)
90 = (X + 1)(90 - 1)
90 = (X + 1)(89)
90 = 89X + 89
90 - 89 = 89X
1 = 89X
X = 1/89
2) 9(3 - X) = 2X²
27 - 9X = 2X²
0 = 2X² + 9X - 27
Donde: a = 2; b = 9; c = -27
![X=\frac{-b\pm \sqrt{b^2-4ac}}{2a} X=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-b%5Cpm+%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![X=\frac{-9\pm \sqrt{9^2-4(2)(-27)}}{2(2)} X=\frac{-9\pm \sqrt{9^2-4(2)(-27)}}{2(2)}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-9%5Cpm+%5Csqrt%7B9%5E2-4%282%29%28-27%29%7D%7D%7B2%282%29%7D)
![X=\frac{-9\pm \sqrt{81+216}}{4} X=\frac{-9\pm \sqrt{81+216}}{4}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-9%5Cpm+%5Csqrt%7B81%2B216%7D%7D%7B4%7D)
![X=\frac{-9\pm \sqrt{297}}{4} X=\frac{-9\pm \sqrt{297}}{4}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-9%5Cpm+%5Csqrt%7B297%7D%7D%7B4%7D)
![X=\frac{-9\pm 3\sqrt{33}}{4} X=\frac{-9\pm 3\sqrt{33}}{4}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-9%5Cpm+3%5Csqrt%7B33%7D%7D%7B4%7D)
X1 = [-9 + 3√33]/4 = 2.058421
X2 = [-9 - 3√33]/4 = -6.558421
3) 2X(X - 5) = X + 3
2X² - 10X = X + 3
2X² - 10X - X - 3 = 0
2X² - 11X - 3 = 0
Donde: a = 2; b = -11; c = -3
![X=\frac{-b\pm \sqrt{b^2-4ac}}{2a} X=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-b%5Cpm+%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![X=\frac{-(-11)\pm \sqrt{(-11)^2-4(2)(-3)}}{2(2)} X=\frac{-(-11)\pm \sqrt{(-11)^2-4(2)(-3)}}{2(2)}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-%28-11%29%5Cpm+%5Csqrt%7B%28-11%29%5E2-4%282%29%28-3%29%7D%7D%7B2%282%29%7D)
![X=\frac{11\pm \sqrt{121+24}}{4} X=\frac{11\pm \sqrt{121+24}}{4}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B11%5Cpm+%5Csqrt%7B121%2B24%7D%7D%7B4%7D)
![X=\frac{11\pm \sqrt{145}}{4} X=\frac{11\pm \sqrt{145}}{4}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B11%5Cpm+%5Csqrt%7B145%7D%7D%7B4%7D)
![X=\frac{11\pm \ 12.04159}{4} X=\frac{11\pm \ 12.04159}{4}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B11%5Cpm+%5C+12.04159%7D%7B4%7D)
X1 = [11 + 12.04159]/4 = 5.7603975
X2 = [11 - 12.04159]/4 = -0.2603975
90 = (X + 1)(90 - 1)
90 = (X + 1)(89)
90 = 89X + 89
90 - 89 = 89X
1 = 89X
X = 1/89
2) 9(3 - X) = 2X²
27 - 9X = 2X²
0 = 2X² + 9X - 27
Donde: a = 2; b = 9; c = -27
X1 = [-9 + 3√33]/4 = 2.058421
X2 = [-9 - 3√33]/4 = -6.558421
3) 2X(X - 5) = X + 3
2X² - 10X = X + 3
2X² - 10X - X - 3 = 0
2X² - 11X - 3 = 0
Donde: a = 2; b = -11; c = -3
X1 = [11 + 12.04159]/4 = 5.7603975
X2 = [11 - 12.04159]/4 = -0.2603975
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años